Changing perceptions of work ability in people with low back pain: a feasbility and economic evaluation - Coole, Carol (2012)
Background: Low back pain is a main cause of sickness absence and work disability in the UK. The economic impact of this is considerable and there is a growing urgency to address the occupational management of low back pain through a vocational focus on rehabilitation. However there is a lack of evidence as to how the needs of this client group can best be met. Objective: The aim of this study was to test the feasibility of delivering an NHS vocational intervention to this client group, assess how acceptable the intervention was to the participants, and examine the costs involved. Methods: The study followed an iterative process of development, evaluation and implementation. The study used survey and interview methods to investigate current NHS provision of work-related advice and support to this client group, and determine how the effectiveness of vocational interventions might be measured. The findings were used to inform the design and test the feasibility of an individually targeted vocational intervention and economic evaluation with patients concerned about their ability to work due to low back pain. Results: The findings of this research demonstrated that there is limited advice and support available to people who are concerned about their ability to work due to low back pain, either from clinicians or in the workplace. Although routine multidisciplinary group rehabilitation reduced patients' concerns, its impact depended on the ability of the patient to apply condition management tools and techniques to the workplace. A total of 51 patients were recruited over a six month period to a feasibility randomised controlled trial with concurrent economic evaluation. Eighty-seven individual work support sessions were delivered. Outcome data was obtained for 38 participants at six month follow-up. Post-trial interviews were conducted with 22 of the trial participants. The intervention and the trial were acceptable to many of the participants, although not all were willing for the researcher to involve the workplace and some did not engage. For some, the demands of work itself were an obstacle to accessing treatment. Conclusions: This study showed that it is feasible to deliver an individually targeted NHS vocational intervention to this client group, that the protocol was acceptable to many of the participants, and that an economic evaluation could be conducted. However, the current design cannot be recommended for a definitive randomised controlled trial. Considerable methodological changes are needed to address the method of recruiting participants, the delivery of the intervention and the measurement tools used. Furthermore, routine rehabilitation may not be sufficiently reliable as a control. Finally, the impact of vocational interventions is likely to be limited unless partnership working between clinicians and employers becomes customary practice.